A taxonomic note on Chinese species of the Neolucanus fuscus group with the description of a new species (Coleoptera: Lucanidae: Lucaninae) - Xin, Fei-Yi; Zhong, Xiao-Tian; Guo, Wen-Chi; Zhang, Yi-Feng; Qi, Zhi-Hao; Wu, Song-Qing (Zootaxa, 2025)
In this paper, we describe a new stag beetle species from Yunnan, China, i.e., Neolucanus horizontalis Xin, Zhong & Qi, new species which exhibits significant structural differences in mandible, labial vestiture, protibia and male genitalia compared to related species. We also provide redescription of the male of N. fuscus Didier, 1926 and N. brochieri Bomans & Miyashita, 1997. Neolucans fuscus zhongguo Schenk, 2012 is synonymized with N. fuscus fuscus Didier, 1926. We also present a distribution map and an identification key for the telodont males of the N. fuscus group. Finally, we discuss the species group affiliation of N. baongocae Nguyen, 2013.